Salt reduction policy for out of home sectors: a supplementary document for the salt reduction strategy to prevent and control non-communicable diseases (NCDS) in Malaysia 2021–2025 - Harun, Zaliha; Shahar, Suzana; You, Yee Xing; Abdul Manaf, Zahara; Abdul Majid, Hazreen; Chin, Chia Yook; Haron, Hasnah; Michael, Viola; Mohamad, Hamdan; Mohd Yazid, Siti Farrah Zaidah; Abdul Manan, Musaalbakri; Wan Ibadullah, Wan Zunairah; et al. (BioMed Central, 2024)
Cardiovascular diseases (CVDs) are the major cause of death among Malaysians. Reduction of salt intake in populations is one of the most cost-effective strategies in the prevention of CVDs. It is very feasible as it requires low cost for implementation and yet could produce a positive impact on health. Thus, salt reduction initiatives have been initiated since 2010, and two series of strategies have been launched. However, there are issues on its delivery and outreach to the target audience. Further, strategies targeting out of home sectors are yet to be emphasized. Our recent findings on the perceptions, barriers and enablers towards salt reduction among various stakeholders including policy-makers, food industries, food operators, consumers and schools showed that eating outside of the home contributed to high salt intake. Foods sold outside the home generally contain a high amount of salt. Thus, this supplementary document is being proposed to strengthen the Salt Reduction Strategy to Prevent and Control Non-communicable Diseases (NCDs) for Malaysia 2021–2025 by focussing on the strategy for the out-of-home sectors. In this supplementary document, the Monitoring, Awareness and Product (M-A-P) strategies being used by the Ministry of Health (MOH) are adopted with a defined outline of the plan of action and indicators to ensure that targets could be achieved. The strategies will involve inter-sectoral and multi-disciplinary approaches, including monitoring of salt intake and educating consumers, strengthening the current enforcement of legislation on salt/sodium labelling and promoting research on reformulation. Other strategies included in this supplementary document included reformulation through proposing maximum salt targets for 14 food categories. It is hoped that this supplementary document could strengthen the current the Salt Reduction Strategy to Prevent and Control NCDs for Malaysia 2021–2025 particularly, for the out-of-home sector, to achieve a reduction in mean salt intake of the population to 6.0 g per day by 2025. © The Author(s) 2024.